Pemanfaatan Tanaman Herbal Sebagai Antibiotik Alami Untuk Meningkatkan Indeks Performa (Ip) Ayam Broiler - Saleh, Muhammad; Pasanda, Octovianus SR (Politeknik Negeri Ujung Pandang, 2019)
The research was aimed to determine the volume and time of giving the natural antibiotic which are optimal for the value of Index Performance (IP) of broiler chickens. The first treatment variable was: giving natural antibiotics with a dose for partition 1 0.05mL / 40 mL water / chicken / day, partition 2 0.1mL / 40 mL water / chicken / day, partition 3 0.15mL / 40 mL water / chicken / day, partition 4 (synthetic antibiotics as a comparison) and carried out for 35 days in a fixed time of 24 hours. Optimal results with the best Index Performance (IP) obtained from the first variable followed by the second treatment variable, the time of giving natural antibiotics for partition 1 given once a day, partition 2 every two days, and partition 3 three days with a constant giving doseÂ 0.15 mL / 40 mL water / chicken / day for 35 days. The parameters observed were: (1) average body weight, (2) weight gain, (3) feed consumption, (4) feed conversion, and (5) number of live chickens. From these data the IP of broiler chickens was calculated and from the two variables obtained the optimal dose and time of giving natural antibiotics. Based on research results from the product, the best of giving natural antibiotic volume is 0.15 mL / chicken or equal to 4.2 mL / 28 chickens which it is able to increase the value of broiler chicken IP until harvest time. From the optimal results obtained in the trial volume variation of giving natural antibiotic, the experiment can be continued with the aim of determining the optimal time of giving herbal antibiotics namely the best results are obtained once a day for 28 chickens because it shows that the giving natural antibiotic is able to increase the IP value of broiler chickens until harvest.